Soil fertility management in Babati: A practical guide on good agricultural management practices in smallholder farming systems - Kihara, Job Maguta; Bolo, Peter Omondi; Kinyua, Michael (2019)
Working with farmers and extension staff within the Ministry of Agriculture and interactions with broad range of researchers across national research and CGIAR Centers operating in Northern Tanzania resulted in a wealth of experience and knowledge that we bring forward in this guide. We have observed wide yield gaps across farms and experienced first-hand key challenges faced by farmers as we worked in their fields, interacted in field days, participatory technology evaluations, exchange visits and brainstorming meetings with farmers. High attainable yields observed by some individual farmers and researchers in experimental and demonstration trials clearly demonstrate potential of applying simple agronomic and other supporting practices to change fortunes of farmers. This is what inspired this guide. Although expressed through simple illustrations and language, most of the data and information are generated through rigorous scientific and data analysis approaches to ensure accuracy of the information. The guide, a knowledge intensive resource, brings together key messages from 6 years of International Center for Tropical Agriculture’s (CIAT) operations in Babati and is a valuable management tool for farmers. It is also an essential reference tool for local agricultural extension and other stakeholders involved in the field of agriculture. The agricultural extension staff reviewed this guide during a workshop held on 17 June 2019 in Babati. These staff included: Jetrida Kyekaka, the District Agriculture, Irrigation and Cooperative Officer (DAICO); Rose Pallangjo, Jonus Masamu and Paulo Tarmo, the District Extension Officers; and Adelta Macha, an extension officer in Gallapo village.